Object of study or foreign matter?: Contributions of philosophical analysis of Yves Schwartz for studies on the work (Cadernos de Psicologia Social do Trabalho, 2011)
The paper features the contributions of the philosopher Yves Schwartz, from his analysis of philosophical studies on the work for reflection on the importance of the knowledge workers to understand the contemporary work. Start with the summary presentation of some authors and ideas favored when taking work and its metamorphoses as the object of study today. In a second step, has a Schwartz paper in which he identified a lineage in the Western philosophical tradition, more than object of study, considered the work as foreign matter, emphasizing the knowledge of workers and the necessary position of humility experts and researchers face the worlds of labour.